Embete og råd - en gjenvisitt.: En analyse av premisser og argumenter i utredningen Kirkens embete og råd (1987). (Tidsskrift for Praktisk Teologi, 2021)
The article takes as its unit of analysis the Norwegian study Ministry and council from 1987, employing concepts from ecclesiology and the knowledge regimes of Tian Sørhaug. The study, with its model for a collaborative relation between ministry and congregations, has had a significant reception history. The article takes as its point of departure that there may have taken place a process of “blackboxing” (Latour), and wants to “open up” the box. We identify ecclesiological premises that emphasize church as universal more than as contextual, and as a space for active participation more than a passive reception of salvation. Further, we discuss a lack of conceptual clarity in the model itself, and to what extent the minister should be seen as a contributor to strategic leadership in the council and the larger “network” around it.